Playful learning : events and activities to engage adults - Whitton, Nicola; Moseley, Alex (Routledge, 2019)
"Offering an innovative and dynamic approach to adult learning, Playful Learning explores the potential of play in adulthood with the goal of helping educators, corporate trainers and event designers incorporate play-based activities for adults into both educational and work settings. Through a comprehensive overview of the value of play in adulthood, this book responds to the growing popularity of playful events for adults in academic and business settings designed to promote higher levels of engagement. Drawing on the authors' own decades of experience at the forefront of the field, this helpful reference incorporates strategies and techniques for bringing play into any learning design. Examples and case studies of successful playful design at conferences, training events, and in higher education illustrate what effective playful event design looks like in practice. With a multi-sector appeal that spans business, education, and entertainment while bringing together practice and theory in an accessible manner, Playful Learning is a must-have resource for researchers, practitioners, managers, and administrators alike"- Resumé vydavatel
Keywords: vzdělávání dospělých; didaktické hry; adult learning; educational games; elektronické knihy; příručky; electronic books; handbooks and manuals